ANALISIS PENGENDALIAN BAHAN BAKU BATU BATA PRESS MENGGUNAKAN METODE MATERIAL REQUIREMENT PLANNING (MRP) - Pangestu, Iqbal agung; Whydiantoro; Rizanuddin Nur, Hafni (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
Bata Merah Press Majalengka was founded in 2012, which was previously called CBL Bata Merah. At that time the production system still used manual production. As time goes by and in line with the large market demand and considering the continuous development in Majalengka, to support this large demand, in 2016 the business actor changed the manual production system to production using a press machine and changed the name of the business to `Bata Merah Press Majalengka. The goal to be achieved in this research is to understand the variables used in raw material inventory planning using the MRP method, applying the Material requirements planning (MRP) method.